2021
DOI: 10.1371/journal.pone.0250530
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of high-risk human papillomavirus on oropharyngeal squamous cell carcinomas in Taiwan: A retrospective cohort study

Abstract: Background and objectives Human papillomavirus (HPV)-driven oropharyngeal squamous cell carcinoma (OPSCC) is increasing globally. In Taiwan, HPV-positive OPSCC is obscured by tobacco, alcohol, and betel quid use. We investigated the role of high-risk HPV (hrHPV) in a large retrospective Taiwan OPSCC cohort. Methods and results The cohort of 541 OPSCCs treated at Chang Gung Memorial Hospital from 1998–2016 consisted of 507 men (94%) and 34 women (6%). Most used tobacco (81%), alcohol (51%), and betel quid (65… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 87 publications
6
12
0
Order By: Relevance
“…This study also explores the incidence trend of HPV positive OPC in a population where HPV negative head and neck cancer is still prevalent. Similar to previous studies, this study shows that the percentage of HPV positive OPC remained stable around 30% for each calendar periods [ 8 12 ] but both incidences of HPV negative OPC and HPV positive OPC are rapidly increasing by about two folds in Taiwan during the period from 1999 to 2014. This low percentage may be one of the reasons why some clinicians do not think that HPV positive OPC is an important head and neck cancer in Taiwan despite the increasing number of HPV positive OPC patients in recent years.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This study also explores the incidence trend of HPV positive OPC in a population where HPV negative head and neck cancer is still prevalent. Similar to previous studies, this study shows that the percentage of HPV positive OPC remained stable around 30% for each calendar periods [ 8 12 ] but both incidences of HPV negative OPC and HPV positive OPC are rapidly increasing by about two folds in Taiwan during the period from 1999 to 2014. This low percentage may be one of the reasons why some clinicians do not think that HPV positive OPC is an important head and neck cancer in Taiwan despite the increasing number of HPV positive OPC patients in recent years.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, our findings revealed that the percentage of HPV positive OPC in Northern Taiwan (33%), where it is more urbanized with higher prevalence of HPV infection and lower prevalence of betel nut chewing [ 16 , 22 ], is higher than that in other regions (22.5%) and rose from 25 to 38% during the period of 1999–2014. This trend is similar to another single hospital-based cohort in Northern Taiwan [ 12 ]. This suggests that the percentage of HPV positive OPC will rise and surpass HPV negative OPC, becoming a common head and neck cancer in the near future.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the western world, OPSCCs are reported to be caused by HPV in the majority of patients, and there was an upsurge of HPV-induced OPSCC in the United States from 16% in the 1980s to more than 70% during the 2000s [ 22 ]. The high incidence of HPV-induced OPSCC is also seen in a number of European countries, with an increase from 35% before 2000 to 73% after 2005 [ 23 ], whereas HPV positivity in Asia is reported to occur in 20–34% of OPSCCs [ 24 , 25 , 26 , 27 ] with an increasing incidence [ 24 , 25 , 27 ].…”
Section: Development Of Hpv Sccupmentioning
confidence: 99%